CONSUMER EVALUATION AND COMPETITIVE ADVANTAGE IN CHINESE BANKING MARKET - XU, PEIWEN (2007)
After December 2006 in line with WTO entry requirements, China is to completely open its banking industry to foreign players and all the restrictions to foreign financial institutions will be eliminated. Foreign banks are qualified to provide a full array of banking service in any currency to retail and wholesale for Chinese citizens throughout the country. Banks like HSBC, Citibank and Standard Chartered will gradually be permitted to offer RMB-based services, first to Chinese companies and then to individuals in more and more cities. By 2007, the international banks and local institutions will be free to vie with one another without limitation. They are going to follow a strategy of local incorporation. Therefore, it is believed that the competition in Chinese retail banking market is primary for foreign banks. The purpose of this paper is to study relative impact of different dimensions of retail financial service offerings provided by foreign banks on the characteristics of the process of customers evaluation and decision making. This paper applied survey as the research method to examine the impact of seven dimensions of retail financial service offerings on the process of customer evaluation. By using questionnaire to collect data from two groups of sample and operating SPSS to analyze the data, statistic findings have been reached. Connecting with the actual situation of Chinese retail banking market and the attitude of Chinese customers, this paper have discussed key findings and present resultant four implications and recommendations for further development of foreign banks in Chinese retail banking market. These recommendations are valuable for foreign banks to design competitive positioning strategy so as to add value to their customers and create their own competitive advantage.